Gender Sebagai Sub-sample: Variabel Anteseden Perilaku Organizational Citizenship Behavior (OCB) - I Nyoman Tri Sutaguna; Agus Yulistiyono; Yenny Verawati; Ni Made Satya Utami; I Made Purba Astakoni (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2022)
The objectives of this study namely analyzing the role of workplace spirituality, organizational citizenship behavior (OCB), organizational commitment, job satisfaction, and analyzing gender roles as a sub-sample in the research model adopted. This research was conducted in all notary offices in Bangli Regency, with research sample of 45 permanent employees. Empirical data were analyzed through the Partial Least Square approach (SEM_PLS) approach. The results of testing the model with the Q-Square Predictive Relevance (Q2), R-Square (R2) approach or the coefficient of determination, and Goodness of Fit (GoF) obtained a model with a good predicate. Research results confirmed that workplace spirituality significantly influence on job satisfaction and organizational citizenship behavior. Results also proved that workplace spirituality positively influence organizational commitment. Whereas job satisfaction insignificantly influences organizational citizenship behavior and organizational commitment also showed insignificant effect towards organizational citizenship behavior. In testing gender as a sub-sample on all linkages built in the model, no significant results have been obtained, in the sense that gender roles (both male and female) as a group are not significantly different.